Quality of urban environment: a case of citizens perception in Satkhira Municipality, Bangladesh. (Chittagong University Journal of Biological Sciences, 2013)
In this study, an attempt has been made to identify the major problems of urban environment in Satkhira Municipality. The perceptual data were collected through field survey based on structural questionnaire. It designed 100 selected respondents and framed 32 environmental variables including 3 points satisfaction index. It was observed from the study that drainage congestion is the major urban environmental problem of Satkhira Municipality and it creates a variety of physical environmental problems such as water logging, increasd soil and water salinity level, water and soil pollution etc. of the area. Because of the absence of certain urban facilities such as employment opportunity, recreational level, shortage of electricity supply (illegal connection, improper meter reading, system loss and load shedding etc.) inadequate local security, city dwellers are found to be dissatisfied. These lead to the generation of various social disorders including hijacking, vandalism and phonongraph, etc. However, there are ample scopes to develop a sustainable (eco-friendly) city keeping these considerations in mind. DOI: http://dx.doi.org/10.3329/cujbs.v6i1-2.17082 The Chittagong Univ. J. B. Sci.,Vol. 6(1&2):65-76, 2011